Monitoring of the Profitability Effect of Tourism Supports in the North Great Plain Region - Nagy, Tünde; Darabos, Éva (International Journal of Engineering and Management Sciences, 2018)
Today the tourism is one of the largest and the most dynamically progressive sector, monitoring of its performance important research area. The sector and its companies’ performance are related tightly, a present study deals with the corporate performance test. Its accurate goal is the monitoring of the profitability effect of 2007-2013.yearly budgetary periods tourism supports in the North Great Plain Region through the example of two of a region’s companies. The basis of the examination the statistical, corporate data which can be reached publicly and data from the questionnaire filled by the companies and data from their competition registrar.